An Unusual Presentation of Spermatocytic Seminoma: A Case Report - Monika Gupta; Nikhilesh Kumar; Honey Bhasker Sharma; Megha Bansal (Dr. Annil Mahajan, 2024)
Spermatocytic Seminoma is a rare yet distinct testicular germ cell tumor which represent less than 01% of testicular tumor. Here we presented a case of testicular swelling in young male. On histopathological examination Spermatocytic Seminoma was confirmed. However, Spermatocytic Seminoma is common is elderly age group. Since the prognosis for this tumor type is favourable, accurate diagnosis and differentiation from other malignant testicular neoplasm (classical seminoma) is must for therapeutic management with long term follow up.